Complete plastome sequence of Lilium pardalinum Kellogg (Liliaceae). Issue 2 (3rd July 2018) - Kim, Hyoung Tae; Zale, Peter J.; Lim, Ki-Byung
Abstract: Lilium pardalinum Kellogg is native to the Pacific Coast of the United States, and grows in woodland near streams. In the present study, the complete plastome of L. pardalinum was sequenced. The plastome sequence is 151, 969 bp long with a large single copy, a small single copy, and two inverted repeat regions of length 81, 401, 17, 346, and 26, 611 bp, respectively. A total of 133 genes were identified, including 82 coding genes, 8 ribosomal RNAs, 38 transfer RNAs, and 5 pseudogenes. Among the 5 pseudogenes, pseudo ndhF and ndhG genes were similar to that of L. washingtonianum and L. philadelphicum, respectively. Lilium pardalinum is sister to American lilies, except L. philadelphicum .